A model for building business customer dependency based on product attributes and distribution relationships - Kurniawan, Rahman; Arief, Mts; Abdinagoro, Sri Bramantoro; Heriyati, Pantri (International Journal of Innovative Research and Scientific Studies, 2025)
This study aims to examine the extent to which product attributes and distributor relationships influence the formation of business customer dependency on bagged cement distributors. The unit of observation in this research is building material stores that regularly sell bagged cement products. The data were collected using a cross-sectional, one-shot approach in 2024. The population consists of 46,118 building material stores that consistently sell bagged cement products. The sample size was determined using the Slovin formula, resulting in 397 respondents. A stratified random sampling technique was applied based on regional work areas. The questionnaire employed a five-point Likert scale. Causal analysis in this study was conducted using Covariance-Based Structural Equation Modeling (CB-SEM). The results indicate that both product attributes and distributor relationships significantly affect business customer dependency, with distributor relationships exerting a stronger influence. This study contributes to the existing literature on business customer dependency, particularly in the context of the bagged cement industry in Indonesia. The findings offer managerial implications for cement distributor management to foster higher-quality relationships with retail stores by strengthening elements of trust, communication, and reliability, as well as enhancing product attributes in terms of packaging, safety, and brand reputation.